Wood Decay Characteristics and Interspecific Interactions Control Bacterial Community Succession in Populus grandidentata (Bigtooth Aspen) - Kuramae, Eiko E.; Leite, Marcio F. A.; Suleiman, Afnan K. A.; Gough, Christopher M.; Castillo, Buck T.; Faller, Lewis; Franklin, Rima B.; Syring, John (Frontiers in Microbiology, 2019)
Few studies have investigated bacterial community succession and the role of bacterial decomposition over a continuum of wood decay. Here, we identified how (i) the diversity and abundance of bacteria changed along a chronosequence of decay in Populus grandidentata (bigtooth aspen); (ii) bacterial community succession was dependent on the physical and chemical characteristics of the wood; (iii) interspecific bacterial interactions may mediate community structure. 459 taxa were identified through Illumina sequencing of 16S rRNA amplicons from samples taken along a continuum of decay, representing standing dead trees, downed wood, and soil. Community diversity increased as decomposition progressed, peaking in the most decomposed trees. While a small proportion of taxa displayed a significant pattern in regards to decay status of the host log, many bacterial taxa followed a stochastic distribution. Changes in the water availability and chemical composition of standing dead and downed trees and soil were strongly coupled with shifts in bacterial communities. Nitrogen was a major driver of succession and nitrogen-fixing taxa of the order Rhizobiales were abundant early in decomposition. Recently downed logs shared 65% of their bacterial abundance with the microbiomes of standing dead trees while only sharing 16% with soil. As decay proceeds, bacterial communities appear to respond less to shifting resource availability and more to interspecific bacterial interactions – we report an increase in both the proportion (+9.3%) and the intensity (+62.3%) of interspecific interactions in later stages of decomposition, suggesting the emergence of a more complex community structure as wood decay progresses.